A more significant role for insertion sequences in large-scale rearrangements in bacterial genomes - Wing Y. Ngan; Lavisha Parab; Frederic Bertels; Jenna Gallie (mBio)
ABSTRACT Insertion sequences (ISs) are mobile pieces of DNA that are widespread in bacterial genomes. IS movements typically involve (i) excision of the IS element, (ii) cutting of target site DNA, and (iii) IS element insertion. This process generates a new copy of the IS element and a short duplication at the target site. It has been noted that, for some extant IS copies, no target site duplications (TSDs) are readily identifiable. TSD absence has been attributed to degeneration of the TSD after the insertion event, recombination between identical ISs, or adjacent deletions. Indeed, the latter two—recombination between ISs and adjacent deletions—are frequent causes for the absence of TSDs, which we demonstrate here in an analysis of genome sequence data from the Lenski long-term evolution experiment. Furthermore, we propose that some IS movements—namely, those that occur in association with large-scale genomic rearrangements—do not generate TSDs, and occur without evidence for recombination between ISs or adjacent deletions. In support of this hypothesis, we provide two direct, empirical observations of such IS transposition events: an IS5 movement plus a large deletion in Escherichia coli C, and an IS481 movement occurring with a large duplication in Pseudomonas fluorescens SBW25. Although unlikely, it is possible that the observed deletion and associated IS movement occurred in two successive events in one overnight culture. However, an IS at the center of a large-scale duplication is not readily explained, suggesting that IS element activity may promote both large-scale deletions and duplications.IMPORTANCEInsertion sequences are the most common mobile genetic elements found in bacterial genomes, and hence they significantly impact bacterial evolution. We observe insertion sequence movement at the center of large-scale deletions and duplications that occurred during laboratory evolution experiments with Escherichia coli and Pseudomonas fluorescens, involving three distinct types of transposase. We raise the possibility that the transposase does not mediate DNA cleavage but instead inserts into existing DNA breaks. Our research highlights the importance of insertion sequences for the generation of large-scale genomic rearrangements and raises questions concerning the mechanistic basis of these mutations.